Advanced biomedical image analysis - Haidekker, Mark A., 1963- (Hoboken, N.J. : John Wiley & Sons, 2011)
"This book covers the four major areas of image processing: Image enhancement and restoration, image segmentation, image quantification and classification, and image visualization. Image registration, storage, and compression are also covered. The text focuses on recently developed image processing and analysis operators and covers topical research"--Provided by publisher.
(Publisher-supplied data) ch. 1. Image analysis : a perspective -- ch. 2. Survey of fundamental image processing operators -- ch. 3. Image processing in the frequency domain -- ch. 4. Wavelet-based filtering -- ch. 5. Adaptive filtering -- ch. 6. Deformable models and active contours -- ch. 7. The Hough transform -- ch. 8. Texture analysis -- ch. 9. Shape analysis -- ch. 10. Fractal approaches to image analysis -- ch. 11. Image registration -- ch. 12. Image storage, transport, and compression -- ch. 13. Image visualization -- ch. 14. Image analysis and visualization software.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Diagnostic imaging -- Digital techniques; Image processing -- Digital techniques; Electronic books